Gestión de talento humano de la movilizadora de frutas tropicales de producción y comercialización la Clementina “Frucomcle”. - Suarez Jame, Jefferson Arcadio (2022)
The present investigation entitled Management of human talent of the Mobilizer of Tropical Fruits of Production and Marketing of the Clementine "FRUCOMCLE" in the parish of La Unión del Cantón Babahoyo, had the objective of making known the existing problems in the company and presenting through the proposal a possible solution as a workaround for resolution. The inductive-deductive methods were used, the synthetic analytical method was applied and also the descriptive method to describe the observations made through the interview with the manager of the company and the survey where 20 worker partners participated. For the processing of information, the Word and Excel tools were used. Synthesis of the research begins with the theoretical support of concepts and theories of various national and international authors in everything related to Human Talent. The research methodology was prepared by qualitative and quantitative modalities, types of research, methods, techniques and tools; which helped to develop a proposal as a possible solution to the problem. The results revealed that there is a need for a Human Talent manager to carry out the planning of activities directed with human capital.